THE EFFECT OF CSR ON ORGANIZATIONAL PERFORMANCE: MEDIATING ROLE OF CORPORATE IMAGE AND MODERATING ROLE OF CORPORATE ACTIVISM - Syeda Shawana Mahasan; Muhammad Farooq Akhtar (International Journal of Contemporary Issues in Social Sciences, 2024)
The objective of this study is to investigate the link between corporate social responsibility and organizational performance using corporate image as mediator and corporate activism as moderator. The study is quantitative in nature, using simple random sampling with 405 manufacturing firm. Data is analyzed through Structural Equation Modelling on SMART PLS 4.0. The study data was obtained from the CEOs and managers of manufacturing firms of Pakistan. The study gives rise to in an indication of the positive outcome of corporate social responsibility execution on organizational performance. Corporate activism is positively associated with corporate image and organizational performance. Hence, it shows that corporates in Pakistan are actively playing their role in sustainable development of the country and hence, increased organizational performance.